2016
DOI: 10.1007/s10745-016-9823-z
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in an Uncertain World: For the Maasai of East Africa, Need-Based Transfers Outperform Account-Keeping in Volatile Environments

Abstract: Using an agent-based model to study risk-pooling in herder dyads using rules derived from Maasai osotua (“umbilical cord”) relationships, Aktipis et al. (2011) found that osotua transfers led to more risk-pooling and better herd survival than both no transfers and transfers that occurred at frequencies tied to those seen in the osotua simulations. Here we expand this approach by comparing osotua-style transfers to another type of livestock transfer among Maasai known as esile (“debt”). In osotua, one asks if i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 28 publications
1
59
1
Order By: Relevance
“…Individuals help one another only when it is mutually advantageous, that is when the cost of helping is less than the benefit of being helped. Additionally, recent evolutionary modellings of risk pooling have revealed the socially optimal nature of helping behaviours [2,5,36,42,60]. They have shown that people's systems of mutual help correspond to the most efficient systems of risk pooling in a volatile environment.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals help one another only when it is mutually advantageous, that is when the cost of helping is less than the benefit of being helped. Additionally, recent evolutionary modellings of risk pooling have revealed the socially optimal nature of helping behaviours [2,5,36,42,60]. They have shown that people's systems of mutual help correspond to the most efficient systems of risk pooling in a volatile environment.…”
Section: Discussionmentioning
confidence: 99%
“…The unpredictability of such situations makes them similar to the kinds of situations in which one might buy an insurance policy. The norms found at many sites may thus be proximate cultural instantiations of this more distal adaptive logic of risk pooling through transfers to those in need (Aktipis et al ; Cronk et al, forthcoming). In others, balanced reciprocity (i.e., direct payback for water) was sometimes expected.…”
Section: Implications Limitations and Next Stepsmentioning
confidence: 99%
“…Ethnographically, better-off foragers tend to share with needy band-mates (28). This forms a system of mutual assistance that minimizes the risk that individuals and families temporarily encountering a string of bad luck will die from need (29,30). These patterns appear to be generated by a universal psychology of sharing that was naturally selected over evolutionary time by the payoff structure of this enduring game.…”
Section: Significancementioning
confidence: 99%